2023
DOI: 10.5530/pres.15.2.040
|View full text |Cite
|
Sign up to set email alerts
|

HPLC-DAD Phenolic Composition, Antioxidant, Anticholinesterase, Antidiabetic and Anti-quorum Sensing Properties of Bitter Kola (Garcinia kola) and Kolanut (Cola acuminata)

Abstract: Background: Eating Cola acuminata and Garcinia cola nuts in African societies symbolizes in socio-cultural hospitality. They stimulate the nervous system, reduce fatigue and sleep. Objectives: To determine the phenolic composition and bioactivities of G. kola and C. acuminata. Materials and Methods: Hydro-ethanol extracts of the nuts were prepared and their phenolic profiles determined using HPLC-DAD. Antioxidant, anticholinesterase, antidiabetic, antimicrobial, antibiofilm and anti-quorum sensing properties w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 78 publications
1
22
0
Order By: Relevance
“…25 In a separate investigation, the observed IC 50 value for kola nut was nearly ten-fold higher, though it is important to note that a positive control was not utilised so the reliability of the enzyme assay system cannot be ascertained. 38 In this systematic review, among the 17 studies that utilised porcine pancreatic α-amylase as the only enzyme, 16,22,23,[25][26][27][34][35][36][37][38][39]41,43,48,50,52 four of them specifically investigated the inhibitory potential of polyphenolic extracts from the edible parts of nuts belonging to the Anacardiaceae family, including pistachio (Pistacia vera), 36,37,48 and Atlantic terebinth (Pistacia terebinthus). 23 The Pistacia genus predominantly inhabits the northern hemisphere, encompasses both evergreen and deciduous varieties, and has long been recognised for medicinal properties.…”
Section: Inhibition Of Porcine Pancreatic and Non-mammalian α-Amylase...mentioning
confidence: 92%
See 3 more Smart Citations
“…25 In a separate investigation, the observed IC 50 value for kola nut was nearly ten-fold higher, though it is important to note that a positive control was not utilised so the reliability of the enzyme assay system cannot be ascertained. 38 In this systematic review, among the 17 studies that utilised porcine pancreatic α-amylase as the only enzyme, 16,22,23,[25][26][27][34][35][36][37][38][39]41,43,48,50,52 four of them specifically investigated the inhibitory potential of polyphenolic extracts from the edible parts of nuts belonging to the Anacardiaceae family, including pistachio (Pistacia vera), 36,37,48 and Atlantic terebinth (Pistacia terebinthus). 23 The Pistacia genus predominantly inhabits the northern hemisphere, encompasses both evergreen and deciduous varieties, and has long been recognised for medicinal properties.…”
Section: Inhibition Of Porcine Pancreatic and Non-mammalian α-Amylase...mentioning
confidence: 92%
“…All three studies by Tsujita et al, used porcine pancreatic α-amylases in addition to human α-amylases. 42,44,45 Additionally, 17 papers explicitly mentioned or referenced the utilisation of porcine pancreatic α-amylases 16,22,23,[25][26][27][34][35][36][37][38][39]41,43,48,50,52 (Table 2). Four studies indicated or referenced the use of α-amylases derived from a bacterial 24,31,47 or fungal source.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…QS network inhibition is a new effect strategy in antimicrobial chemotherapy as it prevents inter-bacterial cells communications and reduces severity and pathogenicity during infections. [79][80][81][82] An easily measurable QS effect involves the production of violacein pigment in C. violaceum CV12472 and the biosensor strain C. violaceum CV026. All the MNPs in this study inhibited violacein production in the two chromobacteria species.…”
Section: Violacein Inhibition Percentages and Quorum-sensing Inhibiti...mentioning
confidence: 99%